Straightforward strategy to substitute amide bonds by 1, 2, 3‐triazoles in peptaibols analogs using Aibψ[Tz]‐Xaa dipeptides. Issue 5 (September 2015) - Ben Haj Salah, Khoubaib; Legrand, Baptiste; Das, Sanjit; Martinez, Jean; Inguimbert, Nicolas
ABSTRACT: Structured peptides gained more attention over a decade because of their biological properties, biocompatibility and ability to act as modulators of protein/protein interactions, antibiotics, analgesics, immunosuppressants or as imaging agents to cite a few relevant applications. However, their poor bioavalability due in part to the susceptibility of the peptide bond to proteolytic cleavages often impaired their development and considerably limited their therapeutic use. To circumvent these problems, many efforts are undertaken to discover stable amide bond mimics resistant to proteolytic degradation. Among them the 1, 2, 3‐triazole emerged as a highly stable analogue of the trans‐peptide bond to generate bioactive peptides. Here we report a convenient approach to readily substitute amide bonds by triazole rings in Aib‐containing peptides using Aibψ[Tz]‐Xaa dipeptide‐like units. We defined their application in solid phase synthesis and generated short model peptide sequences to study the impact of the triazole incorporation on their conformations in solution by circular dichroism and nuclear magnetic resonance spectroscopies. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 104: 611–621, 2015.